Complexidade e contradição na arquitetura brasileira: a obra de Éolo Maia - Bruno Luiz Coutinho Santa Cecilia (2004)
This research presents an study on the work of the Brazilian architect Éolo Maia (1942-2002), from the analysis of four of his buildings: the Verdes Mares Hotel (1976-78) and the Santana do Pé do Morro Chapel (1979-80), both ones situated in the city of Ouro Branco in Minas Gerais, and, in Belo Horizonte, the Barca do Sol (1979-80), building andthe Tancredo Neves Tourist Center (1985-92). In such a way, it develops an architectural analysis methodology presented with the theoretical basis of the research. It tries to evaluate the whole work of this architect considering three periods that keep distinct characteristics. The first period corresponds his formation and the work under influence ofmodernist masters ideals, such as Louis I. Kahn and Le Corbusier. The rupture with modernist canons and the freedom of formal experimentations characterizes the second period. And finally, the third one is characterized by the effective partnership with Jô Vasconcellos and focused in his more recent and mature production, prematurelyinterrupted by his death in September of 2002. This study was divided in three distinct parts: a theoretical, a historicalbiographical, and an analytical one. The first one corresponds to chapter one of thisvolume and looks for establish the basic theoretical landmarks for the elaboration of the research, as well as the methodological script to be used in the analyses of Éolos built works. The second part, developed in chapter two, presents a division of the architects work in three periods, its characteristics and a brief historical and biographical revision ofhis career. Finally, the third part of this research comprehends the chapters three to six, when the four buildings will be altogether analyzed.This study looks for identifies the permanent aspects and the continuities in Éolo Maias work, as well as its ballast in the architectural and artistic culture of Brazil and Minas Gerais, that guarantees its relevance.Finally, this work treats to identify the creative procedures of Éolo Maia and to disclose the essence of its originality founded on the re-signification of usual elements or operational procedures from other architectures, searching, thus, to extend the quarrels concerning the sources of architectural form and its relevancy.